2020
DOI: 10.1002/kjm2.12218
|View full text |Cite
|
Sign up to set email alerts
|

DJ‐1 plays a neuroprotective role in SH‐SY5Y cells by modulating Nrf2 signaling in response to lidocaine‐mediated oxidative stress and apoptosis

Abstract: To investigate the effects of DJ‐1 on lidocaine‐induced cytotoxicity in neurons and the link with Nrf2 signaling, SH‐SY5Y cells were treated with 1, 4, 8, and 16 mM lidocaine. Cell viability was measured by MTT assay, and apoptosis was measured by flow cytometry analysis. The mitochondrial membrane potential, reactive oxygen species (ROS) levels, lipid peroxidation (MDA), and GSH/GSSG ratio were determined with specific kits. Expression of DJ‐1, Nrf2, and Nrf2 downstream signaling proteins (glutathione peroxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…A previous study confirmed that targeting the Keap1/Nrf2 pathway could evidently relieve oxidative stress ( 27 ). Furthermore, it is commonly known that ROS play a crucial role in the activation of numerous biological pathways, and are closely associated with cell proliferation, apoptosis and differentiation ( 28 ).…”
Section: Discussionsupporting
confidence: 55%
“…A previous study confirmed that targeting the Keap1/Nrf2 pathway could evidently relieve oxidative stress ( 27 ). Furthermore, it is commonly known that ROS play a crucial role in the activation of numerous biological pathways, and are closely associated with cell proliferation, apoptosis and differentiation ( 28 ).…”
Section: Discussionsupporting
confidence: 55%
“…Lidocaine has been reported to substantially reduce cell viability in a concentrationdependent manner, though low concentrations ( 1 mM) have not been found to cause significant cytotoxicity. [16][17][18] In the present study, the MTT assay revealed no distinct cytotoxicity at lidocaine concentrations 1 mM. This result was considered in subsequent real-time RT-PCR and western blotting experiments, wherein 0.5 mM lidocaine was investigated, in order to avoid adverse effects on HDPSC survival.…”
Section: Discussionmentioning
confidence: 75%
“…It was shown that eliminating DJ-1 rendered SH-SY5Y susceptibility to cell death [72]. DJ-1 was confirmed to inhibit oxidative stress and consequently leads to cell protection [73,74]. As a fast-reacting oxidation sensor, the degree of its oxidized form (on Cys106) [75] is a proxy for a cell's oxidative status.…”
Section: Discussionmentioning
confidence: 99%